If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -5x + -13 = 15 Reorder the terms: -13 + 2x + -5x = 15 Combine like terms: 2x + -5x = -3x -13 + -3x = 15 Solving -13 + -3x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + -3x = 15 + 13 Combine like terms: -13 + 13 = 0 0 + -3x = 15 + 13 -3x = 15 + 13 Combine like terms: 15 + 13 = 28 -3x = 28 Divide each side by '-3'. x = -9.333333333 Simplifying x = -9.333333333
| -3w+43=-8(w-6) | | 4(x+9)+5=-8(x+9)+17 | | 2/3x=10............x= | | -20=x-28 | | X+Y^50= | | 2=ln(-3x) | | -2(x-5)=-7x-25 | | 4(x-6)-27=8(x-3)-3 | | -2(x-5)=-7x+25 | | 2(x+6)=-4(x+21) | | 2xy=40 | | -2(x+5)=-7x+25 | | 2(x-4)=4(x-7) | | 35+7(x+20)=3x+47 | | 2x*4y=32 | | 3x+31=5(x+10)+25 | | ((91*0.05)+(96*0.05)+(100*0.1)+(95*0.15)+(91*0.15)+(x*0.5))=95 | | -2(x-12)=-8x-30 | | -3x+6=-6x-24 | | 2x*4y=16 | | -2(x+12)=-8x+30 | | -2x-9=-5x+24 | | 1=10-3v | | -2x+9=-5x+24 | | 6x*2=48 | | 16-2g=10 | | (x+(2+i))(x-(2-i))=0 | | 18 = h3+ 15 | | 3x+2y=y-4+5x-y | | 5x^2+y^2=1 | | 32x-12=-18 | | X+3=5+4 |